Regulation of immune response against third-stage Gnathostoma spinigerum larvae by human genes - Puasri, Pattarasuda; Dechkhajorn, Wilanee; Dekumyoy, Paron; Yoonuan, Tippayarat; Ampawong, Sumate; Reamtong, Onrapak; Boonyuen, Usa; Benjathummarak, Surachet; Maneerat, Yaowapa (Frontiers in Immunology, 2023)
Background: Gnathostomiasis is an important zoonosis in tropical areas that is mainly caused by third-stage Gnathostoma spinigerum larvae (G. spinigerum L3).Objectives: This study aimed to prove whether G. spinigerum L3 produces extracellular vesicles (EVs) and investigate human gene profiles related to the immune response against the larvae.We created an immune cell model using normal human peripheral blood mononuclear cells (PBMCs) co-cultured with the larvae for 1 and 3 days, respectively. The PBMCs were harvested for transcriptome sequencing analysis. The EV ultrastructure was examined in the larvae and the cultured medium.Results: Extracellular vesicle-like particles were observed under the larval teguments and in the pellets in the medium. RNA-seq analysis revealed that 2,847 and 3,118 genes were significantly expressed on days 1 and 3 after culture, respectively. The downregulated genes on day 1 after culture were involved in pro-inflammatory cytokines, the complement system and apoptosis, whereas those on day 3 were involved in T cell-dependent B cell activation and wound healing. Significantly upregulated genes related to cell proliferation, activation and development, as well as cytotoxicity, were observed on day 1, and genes regulating T cell maturation, granulocyte function, nuclear factor-κB and toll-like receptor pathways were predominantly observed on day 3 after culture.G. spinigerum L3 produces EV-like particles and releases them into the excretorysecretory products. Overall, genotypic findings during our 3-day observation revealed that most significant gene expressions were related to T and B cell signalling, driving T helper 2 cells related to chronic infection, immune evasion of the larvae, and the pathogenesis of gnathostomiasis. Further in-depth studies are necessary to clarify gene functions in the pathogenesis and immune evasion mechanisms of the infective larvae.